The Sentences of Sextus: a contribution to the history of early Christian ethics - Sextus Pythagoreus ca. 2. Jh.; Chadwick, Henry (Cambridge University Press, 1959)
Sextus's Sentences are a collection of ethical aphorisms which for centuries were read in Latin, Greek, Syriac and Armenian, by Christians from Britain to Mesopotamia. Who 'Sextus' was, and whether he was a Christian, is not certain; Dr Chadwick discusses the evidence, including some he has discovered himself. But the Sentences, probably written in the second century, were widely read in Jerome's time, and were still treated as authoritative in the Middle Ages. They are an important strand in the history of the development of Christian ethics, and are yet another example of that dialogue between the Greek and the Jewish which so profoundly affected the development of the young religion. Dr Chadwick first provides a critical edition of the Greek and Latin texts. There follow studies of the moral teaching of Sextus, the evidence of Origen, the testimony of Rufinus and Jerome, and the internal evidence provided by the texts.